Between rootedness and rootlessness: How sedentarist and nomadic metaphysics simultaneously challenge and reinforce (dual) citizenship claims for Liberia - Pailey, R (Oxford University Press, 2017)
Within the last decade alone, large-scale emigration has emboldened approximately half of all African states to adopt constitutional reforms granting dual citizenship, with some provisions more limited than others. Given Liberia’s post-war prominence in the African Union (AU), Economic Community of West African States (ECOWAS) and Mano River Union (MRU), it remains an important case study on the challenges of consolidating extraterritorial citizenship because of mounting pressure to harmonize its citizenship laws with regional institutions. In this article, I argue that historical and contemporary migration to/from Liberia configured and reconfigured the country’s citizenship norms, thereby generating roots for some, routes for others, and a transnational impasse on dual citizenship. Further, I demonstrate that Liberians’ notions of rootedness and rootlessness have simultaneously facilitated the introduction and postponement in the passage of a contested dual citizenship bill. While the proposed bill is an attempt to reconcile the (forced) migration of hundreds of thousands before, during, and after intermittent armed conflict in Liberia, it has been postponed because, for some, naturalization abroad signifies a rejection of the fundamental tenets of ‘Liberian citizenship’ as being rooted in a singular national identity. Using empirical evidence based on interviews with over 200 Liberians in urban centres in West Africa, North America and Europe, I discuss how the divergent citizenship status choices of respondents represent a continuum of nomadic and sedentarist metaphysical thinking thereby simultaneously strengthening and challenging claims for dual citizenship.